The eleventh commandment eaudiobook - Archer, Jeffrey (Recorded Books Inc., 1989)
Jeffrey Archer's gripping, critically-acclaimed suspense novels have made him one of the top selling authors of the world. He is also a powerful political figure. A former member of Parliament, Archer is a member of the British House of Lords and Deputy Chairman of England's Conservative Party. In The Eleventh Commandment, he takes you on a whirlwind journey from the inner circles of the CIA to the front lines of international espionage. For 28 years, Connor Fitzgerald has led a double life. Behind the mask of a Maryland Insurance executive, Connor has worked as the CIA's most skilled assassin. But now, as Connor follows orders to close in on the new Russian president, he discovers a far more dangerous threat. His boss, the director of CIA, is plotting against him. The eleventh commandment: "Thou shalt not be caught", becomes a challenge that fills Connor's path with nonstop action and danger. Narrator Paul Hecht captures each of the powerful characters and highlights an unforgettable web of intrigue that will keep you enthralled until the final, surprising twist.